2013
DOI: 10.1152/ajprenal.00394.2012
|View full text |Cite
|
Sign up to set email alerts
|

Altered V-ATPase expression in renal intercalated cells isolated from B1 subunit-deficient mice by fluorescence-activated cell sorting

Abstract: Unlike human patients with mutations in the 56-kDa B1 subunit isoform of the vacuolar proton-pumping ATPase (V-ATPase), B1-deficient mice (Atp6v1b1(-/-)) do not develop metabolic acidosis under baseline conditions. This is due to the insertion of V-ATPases containing the alternative B2 subunit isoform into the apical membrane of renal medullary collecting duct intercalated cells (ICs). We previously reported that quantitative Western blots (WBs) from whole kidneys showed similar B2 protein levels in Atp6v1b1(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 47 publications
5
37
0
Order By: Relevance
“…Cells for FACS were further passed through a 35-m filter, and isolation of a clear cell population by FACS was performed at the MGH Flow Cytometry Core facility (Boston, MA). The validity and assessment of contamination of our FACS isolation technique have been shown previously (18,46,59).…”
Section: Methodssupporting
confidence: 53%
“…Cells for FACS were further passed through a 35-m filter, and isolation of a clear cell population by FACS was performed at the MGH Flow Cytometry Core facility (Boston, MA). The validity and assessment of contamination of our FACS isolation technique have been shown previously (18,46,59).…”
Section: Methodssupporting
confidence: 53%
“…It has been shown that the B2 subunit, which is normally co-expressed with the B1 subunit in ICs, compensates for the lack of the B1 subunit of the H + -ATPase in α-ICs and that its activity is sufficient to maintain acid base homeostasis in Atp6v1b1 -/-mice under basal conditions but not in conditions of acid load (20,35) or stimulation of angiotensin II (36). Our data showing no electroneutral NaCl transport in the CCD of Atp6v1b1 -/-mice suggested that the B2 isoform is not capable of compensating for the absence of B1 in β-ICs under all circumstances (normal-and low-salt diet), conditions that may require angiotensin II mediated regulation of H + -ATPases.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in addition to impaired acid secretion by renal intercalated cells, metabolic acidosis, and bone disorders, renal tubular acidosis in its recessive, more severe form, causes neurological defects; sensorineural deafness, and mental retardation (Fry and Karet, 2007). This form of the disease is arises from loss-of-function mutations in the v-ATPase subunits V0a4 and V1B1 (Karet et al, 1999a; Karet et al, 1999b; Stover et al, 2002) and is reproduced in V1B1 −/− and V0a4 −/− mice (Hennings et al, 2012; Lorente-Canovas et al, 2013; Norgett et al, 2012; Paunescu et al, 2012; Vedovelli et al, 2013), which exhibit defective endocytic trafficking and build-up of lysosomal storage material in proximal tubule cells, suggesting lysosomal hydrolase impairment (Hennings et al, 2012). Mice lacking V1B1 display upregulation of the homologous V1B2 isoform (Vedovelli et al, 2013), suggesting a compensatory mechanism to promote v-ATPase assembly when certain v-ATPase components are lost.…”
Section: V-atpase –Related Lysosomal Acidification Failure In Diseasementioning
confidence: 99%